Effect of four tillage methods and two forms of urea placement in an ultisol of savanna on vegetative and flowering traits of three sesame culltivars, Sesamum indicum L. - Méndez Natera, J.; Medina Leota, O.; Fendel Alvarez, J.; Merazo Pinto, J. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
The main objective of this study was to determine the effect of four tillage methods and placement of urea on four vegetative and one flowering traits of three sesame cultivars. The experiment was carried out at Estación Experimental de Sabana, de la Universidad de Oriente, in a sandy loam soil. The statistical design was a split-plot with special arrangement of treatments, and they were assigned to the main plots. These four tillage methods (TM) were: a) Chisel (C): a pass of chisel plow 30 days before sowing and a pass of rotary cultivator one day before sowing (DBS), b) Harrow (H): three passes of H at 30 and 15 days plus one DBS (conventional method), c) minimum tillage (MT): a pass of rotary cultivator one d) Chisel + Harrow: a pass of C 30 days before sowing and three passes of H at 30 y 15, days plus one day before sowing. The subplots were constituted by a factorial arrangement of three cultivars (Cu) viz.,'Glauca', 'Acarigua' and 'Blanca' and two forms of urea placement (FUP), 200 kgl/ha 30 days after sowing: banded into the soil and superficial, for a total of 24 treatments with three replications. A dose of 500 kg/ha of 12-24-12 was applied at the moment of sowing. The weed control was carried out applying Dual, Linurex and Gramoxone at 2.0; 0.5 and 3,0 L/ha respectively one day after sowing, in all the treatments. The results showed that there was not any significant effect for the FUP and none of their interactions with TM and Cu. The biggest plant height (PH) and effective length of loading (ELL) were registered in the TM of C and H for the 3 Cu, while the lowest height to first capsule (HFC) was recorded in the TM of C+H y MT for 'Glauca' y 'Acarigua' and C+H for 'Blanca', the biggest stem diameter (SD) for Cu were in H for 'Glauca', C and H for 'Acarigua' and C for 'Blanca'. On the other hand, 'Glauca' had the biggest PH, 'Blanca' had the lowest HFC and the biggest SD and 'Acarigua' had the biggest ELL. 'Blanca' had earlier blooming and 'Glauca' had later one, and for the TM, plants had earlier blooming in H and later blooming in MT.